Protocol for a randomized crossover study of thigh cuff inflation in experimental hemorrhage: Assessing its potential as a model for zone 3 REBOA - Sara Stadskleiv Torbjørnsen; Sole Lindvåg Lie; Marius Rehn; Jonny Hisdal; Lars Øivind Høiseth (PLoS ONE, 2025)
Resuscitative endovascular balloon occlusion of the aorta (REBOA) is a method to provide temporary control of noncompressible torso hemorrhage in trauma patients. Previous research on REBOA has mainly focused on animals and patients. This study aims to explore whether thigh cuff inflation combined with simulated hemorrhage can serve as an experimental human model for zone 3 REBOA. Lower body negative pressure is a model of hypovolemia. A zone 3 REBOA occludes aorta at its bifurcation, essentially excluding the pelvis and lower extremities from the circulation. Bilateral proximal thigh cuffs will occlude blood vessels to and from the lower extremities. Twenty healthy volunteers will be exposed to bilateral proximal thigh cuff inflation to suprasystolic pressures to simulate the hemodynamic effects of REBOA during experimental hemorrhage using lower body negative pressure (LBNP). Each participant will complete two experimental conditions in a randomized order within one study visit. In the one condition, subjects will undergo only 60 mmHg LBNP for six minutes. In the alternate condition, 60 mmHg LBNP will be applied for six minutes, adding thigh cuff inflation during the final three minutes. Continuous, non-invasive monitoring of systemic hemodynamic parameters—including arterial blood pressure, stroke volume, and heart rate—will be conducted. Cerebral hemodynamics will be assessed by measuring middle cerebral artery blood velocity and cerebral oxygenation. Pain related to thigh cuff inflation will be assessed using a verbal numerical rating scale. The impact of thigh cuff inflation on systemic and cerebral hemodynamics will be evaluated using mixed-effects regression modeling. This study aims to examine the systemic and cerebral hemodynamic effects of combined thigh cuff inflation and lower body negative pressure in healthy volunteers. Based on the feasibility and findings, the potential of this combination as a model for zone 3 REBOA in simulated hemorrhage will be discussed.